Filmowa twórczość fanowska graczy MMORPG - Markocki, Miłosz (Śląskie Studia Polonistyczne, 2017)
The article presents various movie conventions inspired by MMORPG and made by the players. In order to characterize and describe this kind of fun fiction, the author divided the movies into several general categories due to the functions that, according to their makers, the movies are to fulfil. The criterion of production or technological differences was not, thereby, taken into consideration. Such an approach enables the author to accommodate not only machinima movies but also, to some extent, the MMORPG recordings (such as video tutorials). The article aims at general presentation and description of MMORPG players’ fan movies in order to make it more popular among both the game studies and fun studies scholars.